Final answer:
The derivative of f(x) = xe^x using the primary definition of a derivative is (1+x)e^x.
Step-by-step explanation:
The derivative of f(x) = xe^x using the primary definition of a derivative, reduced to its simplest form before taking the limit, can be found using the product rule.
- Apply the product rule which states that the derivative of (uv) is u'v + uv'
- Let u = x and v = e^x
- Find u' and v'
- Substitute the values into the product rule formula
- Simplify the expression to its simplest form
Therefore, the derivative of f(x) = xe^x is (1+x)e^x.